Hepatic arterial infusion enhances DOTATOC radiopeptide therapy in patients with neuroendocrine liver metastases - Kratochwil, Clemens; López-Benítez, Ruben; Mier, Walter; Haufe, Sabine; Isermann, Berend; Kauczor, Hans-Ulrich; Choyke, Peter L.; Haberkorn, Uwe; Giesel, Frederik L. (Endocrine related cancer, 2011)
Intravenously administered radiolabeled peptides targeting somatostatin receptors are used for the treatment of unresectable gastroenteropancreatic neuroendocrine tumors (GEP-NETs). Recently, we demonstrated a high first-pass effect during intra-arterial (i.a.) administration of positron emission tomography (PET) labeled 68Ga-DOTA0-d-Phe1-Tyr3-octreotide (DOTATOC). In this pilot study, we investigated the therapeutic effectiveness of arterial administered DOTATOC, labeled with the therapeutic β emitters 90Y and 177Lu. 90Y- and/or 177Lu-DOTATOC were infused into the hepatic artery of 15 patients with liver metastases arising from GEP-NETs. Response was assessed using DOTATOC-PET, multiphase contrast enhanced computed tomography, magnetic resonance imaging, and the serum tumor marker chromogranin A. Pharmacokinetic data of the arterial approach were assessed using 111In-DOTATOC scans. With the treatment regime of this pilot study, complete remission was achieved in one (7%) patient and partial remission was observed in eight (53%) patients, six patients were classified as stable (40%; response evaluation criteria in solid tumors criteria). The concomitant decrease of elevated serum tumor marker confirmed the radiologic response. Median time to progression was not reached within a mean follow-up period of 20 months. Receptor saturation and redistribution effects were identified as limiting factors for i.a. DOTATOC therapy. The high rate of objective radiologic response in NET patients treated with arterial infusion of 90Y-/177Lu-DOTATOC compares favorably with systemic chemotherapy and intravenous radiopeptide therapy. While i.a. DOTATOC therapy is only applicable to patients with tumors of limited anatomic distribution, the results of this pilot study are a promising development in the treatment of GEP-NET and warrants further investigation of this novel approach.
Gesehen am 08.07.2022